STUDI PERKEMBANGAN PROPERTI PERUMAHAN GRAHA RAYA BINTARO TANGERANG SELATAN - Yudi, Christopher Hans Putraning; Bella, Priyendiswara Agustina; Tjung, Liong Ju (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Graha Raya Bintaro, established in 1997 with a land area of 350 hectares and having developed 2/3 of the total land, is the primary focus of this study titled "Study on the Development of Residential Properties in Graha Raya Bintaro, South Tangerang." The background of the development of this area involves direct field surveys and interviews with the development management to obtain primary data, while secondary data is gathered from literature and open information portals. The research problem formulation focuses on a profound understanding of the development of residential properties in the region. The research methodology includes direct field surveys and interviews with the development management to obtain primary data, while secondary data is collected from literature and open information portals. The research objective is to analyze trends in the development of residential properties, considering factors such as strategic location and quality public facilities. The importance of the location is further reinforced by the plan to develop Phase 3 of the MRT, which will connect Tangerang to Jakarta, starting in August 2024. One of the MRT Phase 3 stations is planned to be built in the vicinity of the study area, approximately 3 kilometers from the study location. In addition to the MRT, there are also plans for additional connecting transportation to assist the community in accessing existing MRT stations. The research findings are expected to provide a holistic view for developers, stakeholders, and prospective buyers in addressing the changing dynamics of the residential property market in Graha Raya Bintaro. Keywords:  growth; houses;  property Abstrak Graha Raya Bintaro, didirikan pada tahun 1997 dengan luas lahan mencapai 350 hektar dan telah membangun 2/3 dari total lahan, menjadi fokus utama studi ini berjudul "Studi Perkembangan Properti Perumahan Graha Raya Bintaro, Tangerang Selatan." Latar belakang pengembangan kawasan ini melibatkan survei langsung ke lapangan dan wawancara dengan manajemen pengembang untuk mendapatkan data primer, sementara data sekunder dikumpulkan dari literatur dan portal informasi terbuka. Rumusan masalah penelitian ini berfokus pada pemahaman mendalam tentang perkembangan properti perumahan di kawasan tersebut. Metode penelitian melibatkan survei langsung ke lapangan dan wawancara dengan manajemen pengembang untuk mendapatkan data primer, sementara data sekunder dikumpulkan dari literatur dan portal informasi terbuka. Tujuan penelitian adalah menganalisis tren perkembangan properti perumahan, dengan mempertimbangkan faktor-faktor seperti lokasi yang strategis dan fasilitas umum berkualitas. Pentingnya lokasi semakin diperkuat dengan rencana pembangunan MRT Fase 3 yang akan menghubungkan Tangerang dengan Jakarta, dimulai pada Agustus 2024. Salah satu stasiun MRT Fase 3 direncanakan akan dibangun di kawasan dekat lokasi studi, sekitar 3 kilometer dari lokasi studi. Selain MRT, juga direncanakan akan ada transportasi penghubung tambahan yang membantu masyarakat mengakses stasiun MRT yang ada. Hasil penelitian diharapkan memberikan pandangan holistik bagi pengembang, pemangku kepentingan, dan calon pembeli dalam menghadapi perubahan dinamika pasar properti perumahan di Graha Raya Bintaro.